2006
DOI: 10.2754/avb200675010107
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite Toxicity to Danio Rerio: Effects of Fish Age and Chloride Concentrations

Abstract: Vosláfiová E., V. Pi‰tûková, Z. Svobodová: Nitrite Toxicity to Danio Rerio: Effects of Fish Age and Chloride Concentrations. Acta Vet. Brno 2006, 75: 107-113.The aim of the present study was to compare the acute nitrite toxicity for Danio rerio at the age of 20 -25 days (larval stage) and 2 -3 months (juvenile stage) at various chloride concentrations. The semistatic method according to OECD 203 was used in the tests. Nitrite (NO 2 -) is a naturally occurring anion in fresh and saline waters, its concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
1
6
0
3
Order By: Relevance
“…In our trial we focused only on the influence of nitrite on fish growth. In previous experiments 96hLC50 values of NO 2 -were determined in juvenile zebrafish (Voslářová et al 2006). The acute NO 2 -toxicity to D. rerio aged 20-25 days as expressed by the 96hLC50 was 386.00 ± 29.75 mg·l -1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our trial we focused only on the influence of nitrite on fish growth. In previous experiments 96hLC50 values of NO 2 -were determined in juvenile zebrafish (Voslářová et al 2006). The acute NO 2 -toxicity to D. rerio aged 20-25 days as expressed by the 96hLC50 was 386.00 ± 29.75 mg·l -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Acute toxicity of nitrite has been investigated and described in a number of fish species (Bowser et al 1983;Crawford and Allen 1977;Russo and Thurston 1977;McConnell 1985;Lewis and Morris 1986;Kroupová et al 2005;Pištěková et al 2005;Kroupová et al 2006;Voslářová et al 2006), but the effects of chronic nitrite exposure on their survival and growth have not been well documented yet. However, detailed knowledge of the impact of water quality factors on fundamental production characteristics such as growth performance, food conversion efficiency, and animal welfare is needed in order to effectively exploit the benefits of aquacultural systems (Siikavuopio and Saether 2006).…”
Section: Cyprinus Rerio Zebrafish No 2 - Growth Testmentioning
confidence: 99%
“…Wang et al (2006) (Voslářová et al 2006) or in chinook salmon (Oncorhynchus tshawytscha) (Crawford and Allen 1977). Svobodová et al (2005) have suggested some measures that should be done to prevent nitrite poisoning in fish.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of nitrites for fish differs in dependence of many internal and external factors such as water quality, fish species, their size and individual sensitivity (Lewis and Morris 1986;Jensen 2003;Voslářová et al 2006). The most important factor influencing nitrite toxicity is the concentration of chloride ions in water.…”
mentioning
confidence: 99%
See 1 more Smart Citation